Given the following two ordered pairs calculate the rate of the function.
(−9, −4) and (−3, −16)
Enter your answer in the box.
M=

Given the linear function equation state the function rate.
y=−7x+1
Enter your answer in the box.
M=

Given the linear function table state the y-intercept.
x= -2, -1, 0, 1, 2
y=-6, 0, 6, 12, 18
Enter your answer in the box.
b=

Given the linear function Table state the function rate.
x= -2, -1, 0, 1, 2
y=-6, 0, 6, 12, 18
Enter your answer in the box.
m=

Select the linear function equation for the table.
x= -4, -3, -2, -1, 0
y= 7, 4, 1, -2, -5

y=−5x−3

y=3x+5

y=5x+3

y=−3x−5

Respuesta :

Linear functions are functions that have uniform and constant rates.

(a) Ordered pairs

The ordered pair is given as (-9,-4) and (-3,-16).

The slope (m) is calculated as:

[tex]m = \frac{y_2 -y_1}{x_2 -x_1}[/tex]

So, we have:

[tex]m = \frac{-16 --4}{-3--9}[/tex]

[tex]m = \frac{-12}{6}[/tex]

[tex]m = -2[/tex]

Hence, the slope (m) is 2

(b) The rate of y = -7x + 1

The function is given as [tex]y = -7x + 1[/tex]

A linear function is represented as:

[tex]y = mx + b[/tex]

Where m represents the slope/rate

By comparison

[tex]m = -7[/tex]

Hence, the rate (m) is -7

(c) The y-intercept of a linear function

The y-intercept of a linear function is where the x-value is 0

From the table,

y = 6 when x = 0

Hence, the y-intercept (b) is 6

(d) Rate of a linear function

From the table, we have the following ordered pairs

(2,18) and (0,6).

The slope (m) is calculated as:

[tex]m = \frac{y_2 -y_1}{x_2 -x_1}[/tex]

So, we have:

[tex]m = \frac{6 -18}{0-2}[/tex]

[tex]m = \frac{-12}{-2}[/tex]

[tex]m = 6[/tex]

Hence, the slope (m) is 6

(e) Equation of a linear function

From the table, we have the following ordered pairs

(0,-5) and (-3,4).

The slope (m) is calculated as:

[tex]m = \frac{y_2 -y_1}{x_2 -x_1}[/tex]

So, we have:

[tex]m = \frac{4 --5}{-3-0}[/tex]

[tex]m = \frac{9}{-3}[/tex]

[tex]m = -3[/tex]

The equation is then calculated as:

[tex]y = m(x - x_1) + y_1[/tex]

So, we have:

[tex]y = -3(x - 0) -5[/tex]

[tex]y = -3x -5[/tex]

Hence, the linear equation is [tex]y = -3x -5[/tex]

Read more about linear equations at:

https://brainly.com/question/14323743

ACCESS MORE